Usefulness of a Virtual Reality Percutaneous Trigeminal Rhizotomy Simulator in Neurosurgical Training. Issue 3 (September 2015) - Shakur, Sophia F.; Luciano, Cristian J.; Kania, Patrick; Roitberg, Ben Z.; Banerjee, P. Pat; Slavin, Konstantin V.; Sorenson, Jeffrey; Charbel, Fady T.; Alaraj, Ali
Abstract : BACKGROUND: Simulation-based training may be incorporated into neurosurgery in the future. OBJECTIVE: To assess the usefulness of a novel haptics-based virtual reality percutaneous trigeminal rhizotomy simulator. METHODS: A real-time augmented reality simulator for percutaneous trigeminal rhizotomy was developed using the ImmersiveTouch platform. Ninety-two neurosurgery residents tested the simulator at American Association of Neurological Surgeons Top Gun 2014. Postgraduate year (PGY), number of fluoroscopy shots, the distance from the ideal entry point, and the distance from the ideal target were recorded by the system during each simulation session. Final performance score was calculated considering the number of fluoroscopy shots and distances from entry and target points (a lower score is better). The impact of PGY level on residents' performance was analyzed. RESULTS: Seventy-one residents provided their PGY-level and simulator performance data; 38% were senior residents and 62% were junior residents. The mean distance from the entry point (9.4 mm vs 12.6 mm, P = .01), the distance from the target (12.0 mm vs 15.2 mm, P = .16), and final score (31.1 vs 37.7, P = .02) were lower in senior than in junior residents. The mean number of fluoroscopy shots (9.8 vs 10.0, P = .88) was similar in these 2 groups. Linear regression analysis showed that increasing PGY level is significantly associated with a decreased distance from the ideal entry point ( P = .001), a shorter distance from target ( P = .05), a better final score ( P = .007), but not number of fluoroscopy shots ( P = .52). CONCLUSION: Because technical performance of percutaneous rhizotomy increases with training, we proposed that the skills in performing the procedure in our virtual reality model would also increase with PGY level, if our simulator models the actual procedure. Our results confirm this hypothesis and demonstrate construct validity. ABBREVIATION: PGY, postgraduate year